Designing Materials for Vocational Students to Enhance Virtual Learning Experience Utilising Android for Studying English - Sitorus, Nurianti; Andrian; Sinambela, Yusnia; Juwairiah (Bahasa Indonesia, 2024)
Materials are needed to help students in understanding the object of their lessons. In vocational education, English is regarded as one of the subject intended to specific purpose which depends on the major of the students. To that aim, specific materials are more vital compared to the general one. This present study lies the main objective to design the materials to study English virtually for business in Politeknik Negeri Media Kreatif. Similarly, it is also projected to create an application with android-based system which can be used either online or offline. Before designing the materials, students were asked to answer the questions which help the researcher to sort out kinds of topics included. There are forty students involved in an interview. By applying qualitative method, it is found that most of the students look for the authentic-related materials to study English. In order to fulfil that, the researcher finally designed and made the concept to the materials selected. The result indicates that students in vocational need more specific materials which attractive and practical based. Additionally, this research is projected to shed the light on how to enhance the learning experiences of vocational students in virtual learning.